Urban Areas' Readiness in Providing Learning Accommodations for Students with Disabilities Post-COVID-19 Pandemic - Sholihah, Lintang Al mar'atus; Ningsih, Kholifatul Novita; Hardiani, Wahyu; Insani, Nur Hanifah; Husnaini, Azizah Nurul (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The shift in learning models following the COVID-19 pandemic, which occurred without adequate preparation, has added new challenges for students with special needs. As an educational institution in an urban area, Jakarta State University should be an ideal example of an inclusive campus. Although opportunities for students with special needs to enroll have expanded, this has not been matched by specific preparations for learning accommodations. This study aims to identify the challenges faced by students with special needs in obtaining appropriate learning accommodations. Additionally, this study seeks to explore the shift in learning accommodation needs of students with special needs post-pandemic COVID-19. A mixed-method research approach was selected, with quantitative data as the primary focus. Data collection was conducted through questionnaires and interviews, while quantitative data analysis utilized descriptive statistical analysis. The research subjects consisted of 34 students with special needs from eight faculties, enrolled between 2018 and 2024. The students with special needs involved in this study had visual impairments, hearing impairments, physical impairments, low vision, ADHD, learning difficulties, and autism. The results of the study showed diversity in learning accommodation needs for each type of special need. However, these differences could be predicted based on the type and level of special needs. The five aspects studied—course materials, teaching methods, facilities and equipment, peer support, and the need for self-regulation skills—highlight the importance of further attention from the university. These aspects of learning accommodations reflect a shift in learning modes influenced by the COVID-19 pandemic. This shift adds challenges for students with special needs in preparing themselves for the workforce.